The potential stigmatizing effect of the Treaty on the Prohibition of Nuclear Weapons. Issue 5 (2nd September 2018) - Sauer, Tom; Reveraert, Mathias
ABSTRACT: On July 7, 2017, seventy-two years after the start of the nuclear era, 122 states concluded the Treaty on the Prohibition of Nuclear Weapons (TPNW, or "ban treaty"). The treaty forbids the development, production, acquisition, possession, transfer, testing, use, and threat of use of nuclear weapons. Advocates of the TPNW understand that it will not automatically lead to a world without nuclear weapons. The treaty's main goal is to stimulate a societal and political debate inside the nuclear-armed states and their allies by strengthening the antinuclear norm and by stigmatizing nuclear weapons and their possessors. This article assesses to what extent this process of stigmatization might take place. It starts by elaborating on the concepts of stigma and stigmatization. It then matches the concept of stigma with nuclear weapons, and with the humanitarian initiative behind the momentum that led to the TPNW. The article concludes by looking to different stigma-management approaches that can be used by the nuclear-armed states and their allies.